2017
DOI: 10.1101/150664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triazavirine supramolecular complexes as modifiers of the peptide oligomeric structure

Abstract: In this study we present molecular dynamics simulations of the antiviral drug triazavirine, that affects formation of amyloid-like fibrils of the model peptide (SI). According to our simulations, triazavirine is able to form linear supramolecular structures which can act as shields and prevent interactions between SI monomers. This model, as validated by simulations, provides an adequate explanation of triazavirine's mechanism of action as it pertains to SI peptide fibril formation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
8
2
Order By: Relevance
“…2 In the course of studies on TZV activity using model peptides by our colleague, Dr. Olga Alexandrovna Mirgorodskaya, an observation was made that the drug stimulates the precipitation of the peptide from solution. Because this observed TZV effect was contrary to what we previously documented when studying its effects on a peptide comprising an ionic self-complementary motif [5], [6], we decided to analyze the effect in detail. The formation of strong hydrogen bonds between arginine and TZV (mentioned in [5]) could explain aggregation of the generally hydrophobic peptide by a mechanism in which there is shielding of the electrostatic repulsion between arginines.…”
Section: Introductioncontrasting
confidence: 58%
See 2 more Smart Citations
“…2 In the course of studies on TZV activity using model peptides by our colleague, Dr. Olga Alexandrovna Mirgorodskaya, an observation was made that the drug stimulates the precipitation of the peptide from solution. Because this observed TZV effect was contrary to what we previously documented when studying its effects on a peptide comprising an ionic self-complementary motif [5], [6], we decided to analyze the effect in detail. The formation of strong hydrogen bonds between arginine and TZV (mentioned in [5]) could explain aggregation of the generally hydrophobic peptide by a mechanism in which there is shielding of the electrostatic repulsion between arginines.…”
Section: Introductioncontrasting
confidence: 58%
“…The simulation results showed that in the presence of self-organizing supramolecular chains of TZV, the pairwise distance between the centers of mass of the MLT molecules decreases (Figure 3a). It should be noted that some TZV molecules are strongly connected with MLT ( Figure 3b 8 It should be noted that in our earlier work [6], the antiaggregation effect of TZV chains on SI peptide (GDIRIDIRIDIRG) is also due to the interaction of TZV with positively charged a.a.r. The distances from the a.a.r.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Despite the lack of any pre-clinical efficacy data and the absence of the drug target in SARS-CoV-2, clinical trials are underway in China to evaluate its effectiveness for moderate to severe COVID-19 pneumonia. Triazavirin, a guanine nucleotide analog, is currently being assessed in a multicenter randomized clinical trial despite that available data is limited to its antiviral activity against influenza viruses ( Kiselev et al., 2012 ; Shvetsov et al., 2018 ).…”
Section: Drugs Under Investigation For Treatment and Management Of Comentioning
confidence: 99%
“…[6] Clevudine, also known under the trade names Levovir and Revovir, is an antiviral drug for hepatitis B treatment in South Korea and the Philippines. Triazavirin has been proved performing high efficacy towards influenza A and B, including the highly developed H 5 N 1 strain [7][8][9][10] in Russia. Because of the structural similarities between SARS-CoV-2 and H 5 N 1 , health officials are conducting studies on Triazavirin as a potential drug candidate to combat SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%